Barbados : Staff Report for 2013 Article IV Consultation. - International Monetary Fund. Western Hemisphere Dept. (Washington, D.C. : International Monetary Fund, 2014)
This 2013 Article IV consultation highlights Barbados' weak economic performance and high public debt. Foreign reserves are under pressure as fiscal and external imbalances widened in 2012 and further in 2013. Recognizing the need for urgent action, the authorities announced ambitious budget consolidation proposals in 2013 aimed at strengthening the fiscal position and arresting the slide in reserves. Recent fiscal measures, if fully implemented, should stabilize debt levels by 2016. However, downside risks are considerable, and failure to implement corrective policies could result in a disorderly adjustment process. Even with full implementation, fiscal financing pressures and external sector sustainability would remain challenging.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet